Perancangan Sistem Informasi Pengagendaan Surat Masuk dan Surat Keluar di Dinas Pendidikan Kabupaten Asahan - Cici Cahyati Hasibuan (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
This research aims to design an information system for scheduling incoming and outgoing letters at the Asahan District Education Office. Currently, the process of managing letters is still done manually by writing them into a ledger which is inefficient in terms of time and energy. This research uses qualitative methods with data collection techniques through observation, interviews and literature study. The system was designed using the PHP programming language and Unified Modeling Language (UML) for system modeling. The research results show that the designed information system can provide a solution to the problem of managing letters manually by making the data management process easier and faster. This system includes incoming and outgoing mail management features, user management, and report generation, which can improve employee performance in mail administration tasks.